2009
DOI: 10.1063/1.3191670
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond switching in GeTe phase change memory cells

Abstract: The electrical switching behavior of GeTe-based phase change memory devices is characterized by time resolved experiments. SET pulses with a duration of less than 16 ns are shown to crystallize the material. Depending on the resistance of the RESET state, the minimum SET pulse duration can even be reduced down to 1 ns. This finding is attributed to the increasing impact of crystal growth upon decreasing switchable volume. Using GeTe or materials with similar crystal growth velocities, hence promises nonvolatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
268
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(283 citation statements)
references
References 12 publications
1
268
1
5
Order By: Relevance
“…They are known to exhibit a fast amorphous-crystalline phase transition which can be electrically triggered. 80,81 Recently, Polking et al demonstrated that…”
Section: Germanium Telluridementioning
confidence: 99%
“…They are known to exhibit a fast amorphous-crystalline phase transition which can be electrically triggered. 80,81 Recently, Polking et al demonstrated that…”
Section: Germanium Telluridementioning
confidence: 99%
“…These memory technologies are based on the large resistivity contrast between the two phases of the active material-mostly chalcogenide alloys such as Ge 2 Sb 2 Te 5 . In addition, the ability to switch reversibly [3,4] and quickly [5] between the two phases by the application of electrical stimuli renders these materials good candidates for electrical data storage. Herein, the crystalline, low resistance (SET) state is reached from the amorphous, high resistance (RESET) phase via an electrical breakdown effect ("threshold switching") followed by Joule-heating and subsequent fast crystallization, whereas the RESET state is reached by melting the material with a large current followed by rapid cooling ("melt-quenching").…”
Section: Introductionmentioning
confidence: 99%
“…By choosing the materials Ge 2 Sb 2 Te 5 , and AgIn-doped Sb 2 Te (more precisely Ag 4 In 3 Sb 67 Te 26 ) we furthermore aim at studying the apparent contradiction between the two aforementioned experiments [31,32]. The third material, GeTe, is studied due to its promising switching characteristics [5]. In the literature the majority of experiments are done in melt-quenched amorphous phase change memory cells.…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometric compounds along the pseudo-bianry line between GeTe and Bi 2 Te 3 are Ge 27 9 , which were analyzed by ICP-AES. The Bi content in the film is decreased from 18.2% to 17.5% and the Te content also reduced from 54.5% to 49.8% for the ratio of 3:1.…”
Section: Resultsmentioning
confidence: 99%
“…The N 7.9 (Ge 46.9 Bi 7.2 Te 45.9 ) film can be considered as a nitrogen doped GeTe film with addition of Bi. Previous report showed that a GeTe film is a growth dominant material with very short time of set programming less than 16 nsec, 27 which is significantly delayed up to several µsec in N 12 Ge 48 Te 40 film due to the presence of Ge-N bonding. 28,29 In comparison, the N 7.9 (Ge 46.9 Bi 7.2 Te 45.9 ) film showed a very short time of set programming as much as 14 nm upon being employed in our PCM devices.…”
Section: Resultsmentioning
confidence: 99%